Authentication and key distribution protocol based on Diffie-Hellman algorithm and physically unclonable function - Victor A. Yakovlev; Dina Zh. Satybaldina; Eldor Egamberdiyev; Yerzhan Seitkulov (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
Based on the modified Diffie-Hellman (DH) protocol, a key distribution scheme between two correspondents over open communication channels is considered. The correspondents communicate through a trusted entity. An attacker can control the communication channels between the correspondents and the channels between the correspondents and the trusted authority (TA) and perform active attacks there, including a man-in-the-middle attack. DH authentication protocol using physically unclonable functions (PUF) is proposed. A formalized PUF model based on the class of universal hash functions is presented. Namely, it is proposed to use the class of strictly universal hash functions developed by Wegman and Carter. A polynomial dependence of the possible number of PPUs on the number of answers has been proven. Requirements for PPUs suitable for authentication systems are formulated. The protocol has been analyzed, and its security has been proved